Reestablishing Diagnostic Anatomical Pathology Services by a Fine-Needle Aspiration Clinic in Monrovia, Liberia. (21st September 2018) - Fischer, Gabor; Beddoe, Annmarie; Alele, David
Abstract: Objective/Background: Two civil wars and the Ebola epidemic left Liberia with essentially no reliable anatomical pathology services. There had been absolutely no cytology, histology, or forensic services in Monrovia, the nation's capital. Methods: The needs have been assessed and a long-term plan was made by consulting the local physicians and administrators. Potential workforce and financial resources have been identified along with the most suitable location to set up a fine-needle aspiration (FNA) clinic as the first step to rebuild the diagnostic services. Results: The first FNA was performed on January 8, 2018, in the JFK Hospital in Monrovia, and it was followed by 64 other procedures until the end of February. Forty-nine female and 16 male patients went through the diagnostic procedures. Forty-four samples resulted in a benign and 14 in a malignant diagnosis, while 7 were nondiagnostic. Diff-Quick stain was used to prepare the slides, and due to the limitations, cell blocks were not performed for ancillary studies. The diagnostic pathology reports can assist the clinicians now to build a better treatment plan for the patients, and they will also help to build a national diagnostic database. Conclusions: Liberia's health care is still in very poor shape, and the lack of reliable diagnostic services is one of the biggest challenges. FNA has turned out to be a cost-effective method to provide a diagnostic assessment. However, in the long run, consistent planning, persistent joint efforts by the local and foreigner organizations and physicians, and a lot of volunteer help will be needed to improve the pathology services and education in the country.